Assessing the measurement properties of PROMIS Computer Adaptive Tests, short forms and legacy patient reported outcome measures in patients undergoing total hip arthroplasty - C. Braaksma; N. Wolterbeek; M. R. Veen; R. W. Poolman; Y. Pronk; A. D. Klaassen; R. W. J. G. Ostelo; C. B. Terwee (SpringerOpen, 2024)
Abstract Background The commonly used ('legacy') PROMs evaluating outcomes of total hip arthroplasty (THA), have several limitations regarding their measurement properties and interpretation of scores. One innovation in PROMs is the use of Computerized Adaptive Testing (CAT). The Patient-Reported Outcomes Measurement Information System (PROMIS®) is a validated system of CATs. The aim of this study was to assess the measurement properties of PROMIS and legacy instruments in patients undergoing THA. Methodology Patients in this multicenter study filled out a questionnaire twice, including Dutch-Flemish PROMIS v1.2 Physical Function (PROMIS-PF) and v1.1 Pain Interference (PROMIS-PI) CATs and short forms, PROMIS v1.0 Pain Intensity, and legacy PROMs (Hip disability and Osteoarthritis Outcome Score (HOOS), HOOS-Physical function Shortform (HOOS-PS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Oxford Hip Score (OHS), and two numeric rating scales measuring pain). The reliability, measurement precision (Standard Error of Measurement (SEM)), smallest detectable change (SDC), and burden of PROMIS instruments were presented head-to-head to legacy PROMs. Furthermore, construct validity was assessed. Results 208 patients were included. All instruments had a sufficient test-retest reliability (range ICC: 0.83-0.96). The SEM of PROMIS CATs and short forms ranged from 1.8 to 2.2 T-score points, the SEM of legacy instruments 2.6-11.1. The SDC of PROMIS instruments ranged from 2.1 to 7.3 T-score points, the SDC of legacy instruments 7.2-30.9. The construct validity of PROMIS CAT and short forms were found sufficient, except for the PROMIS-PI short form. The burden of PROMIS CATs was smaller than PROMIS short forms (range 4.8-5.2 versus 8-20 items, respectively). The burden of legacy instruments measuring physical functioning ranged from 5 to 40 items. Conclusions The PROMIS-PF is less burdensome, with high measurement precision, and almost no minimal or maximal scores, and an equal reliability compared to legacy instruments measuring physical functioning in patients undergoing THA. The PROMIS Pain Intensity 1a is comparable to the legacy pain instruments in terms of burden, reliability and SDC. Measuring the construct Pain Interference may not have additional value in this population because of its high correlation with instruments measuring physical functioning. The SDC values presented in this study can be used for individual patient monitoring.